The burden of non-specific chronic low back pain among adults in KwaZulu-Natal, South Africa: a protocol for a mixed-methods study - Morris Kahere; Themba Ginindza (BMJ Open)
Introduction Low back pain (LBP) is a major public health concern, affecting individuals of all age groups across the world. In about 90% of LBP cases, there is no specific cause identified and is, therefore, referred to as non-specific LBP. Due to the non-specific nature of LBP, investigations such as radiological and laboratory investigations are unnecessary and results to delayed diagnosis and improper treatment culminating in LBP progressing into chronic LBP (CLBP). LBP is now the leading cause of disability with a significant socioeconomic burden. Despite all these challenges, CLBP is regarded as a trivial condition in low-and-middle-income countries and remains poorly investigated. The distribution of CLBP in Africa is unclear.Methods and analysis The research will be conducted in two phases. The initial phase will be an observational, cross-sectional hospital-based study that will be recruiting 650 participants, to determine the prevalence and risk factors of CLBP. A standardised questionnaire will be used to collect baseline data on the socio-demographic characteristics of participants and other variables of interest (exercise history, occupational posture, level of education and the income status). Disability will be assessed using the Oswestry Disability Questionnaire and the psychological risk factors will be assessed using the Illness-Behaviour Questionnaire (IBQ) and the Fear-Avoidance Belief Questionnaire (FABQ). The second phase will be a retrospective, top-down, prevalence-based cost-of-illness study of the 2018–2019 health records, to estimate the burden of CLBP from the healthcare system’s perspective. The SPSS V.25.0 statistical package will be used for data entry and analysis. Statistical analysis will include descriptive statistics by means of graphs and cross tabulations, inferential statistics by means of logistic regression and χ2 test. A p value of 0.05 will be deemed statistically significant.Ethics and dissemination This protocol was approved by the University of KwaZulu-Natal’s Biomedical Research Ethics Committee (Ref. No.: BREC/00000205/2019) and the KwaZulu-Natal Department of Health Research Ethics (Ref. No.: KZ_201909_002). This will be the first LBP cost-of-illness study in the sub-Saharan Africa, and, therefore, it will close these knowledge gaps and present important evidence on the estimated burden of CLBP in this context. The results of this study will be presented to the Department of Health and to the respective stakeholders and decision-makers to discuss the findings and draw their attention to the prioritisation of LBP research, its management, prevention programmes and implementation of educational programme and for the planning of cost-containment policies.